2022
DOI: 10.3389/fneur.2022.981488
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical features decide the atypical seizure manifestation of parahypothalamic hamartomas

Abstract: BackgroundThe intrahypothalamic phenotype of hypothalamic hamartomas (HH) is associated with epilepsy, and the parahypothalamic phenotype usually leads to central precocious puberty but not neurological comorbidities or seizures. No study has confirmed the pathological role of parahypothalamic hamartomas in epileptogenesis, and the underlying mechanism is yet to be elucidated.ObjectiveWe aimed to investigate whether parahypothalamic hamartomas are intrinsically epileptogenic and elucidate the underlying pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Stereotactic depth recordings of seizure onset and direct HH stimulation have additionally provided direct evidence for GS ictogenesis, 11–13 while electrical 14 and ictal SPECT 15 studies of HH patients have shown that the interface between the HH and the hypothalamus, rather than the entirety of the HH, was associated with seizure incidence 15 . This is consistent with the finding that intrahypothalamic HH lesions are related to GS onset more often than are parahypothalamic HH cases, as was observed in this study and other past reports 4,6,16 . As such, efforts to ablate primarily this interface region and to establish a disconnect via endoscopic surgery, stereotactic radiofrequency thermocoagulation, 12 or laser interstitial thermotherapy 17,18 is clinically viable.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Stereotactic depth recordings of seizure onset and direct HH stimulation have additionally provided direct evidence for GS ictogenesis, 11–13 while electrical 14 and ictal SPECT 15 studies of HH patients have shown that the interface between the HH and the hypothalamus, rather than the entirety of the HH, was associated with seizure incidence 15 . This is consistent with the finding that intrahypothalamic HH lesions are related to GS onset more often than are parahypothalamic HH cases, as was observed in this study and other past reports 4,6,16 . As such, efforts to ablate primarily this interface region and to establish a disconnect via endoscopic surgery, stereotactic radiofrequency thermocoagulation, 12 or laser interstitial thermotherapy 17,18 is clinically viable.…”
Section: Discussionsupporting
confidence: 91%
“… 15 This is consistent with the finding that intrahypothalamic HH lesions are related to GS onset more often than are parahypothalamic HH cases, as was observed in this study and other past reports. 4 , 6 , 16 As such, efforts to ablate primarily this interface region and to establish a disconnect via endoscopic surgery, stereotactic radiofrequency thermocoagulation, 12 or laser interstitial thermotherapy 17 , 18 is clinically viable. The present results also confirmed that the intraventricular portion of HH lesions was primarily associated with epilepsy disease evolution.…”
Section: Discussionmentioning
confidence: 99%